2021
DOI: 10.1002/jsfa.11177
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of crustacean tropomyosin in foods using high‐performance liquid chromatography–tandem mass spectrometry method

Abstract: BACKGROUND Allergic reactions to crustacean products have been increasing owing to the rising consumption. Tropomyosin (TM) is the main crustacean allergen; it has a coiled‐coil structure, which shows stability to various food processing methods. Crustacean processed products have been used in several food products, thereby causing greater difficulties in detecting TM in these products. We aimed to develop an assay based on high‐performance liquid chromatography–tandem mass spectrometry for the accurate and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…These two methods do not measure the same compounds. Tropomyosin is composed of two polypeptide chains, with five peptides found after digestion [ 37 ]. Among them, the peptide with the IVELEEELR sequence has been shown to be the most sensitive and was thus chosen to be a marker of tropomyosin [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two methods do not measure the same compounds. Tropomyosin is composed of two polypeptide chains, with five peptides found after digestion [ 37 ]. Among them, the peptide with the IVELEEELR sequence has been shown to be the most sensitive and was thus chosen to be a marker of tropomyosin [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tropomyosin is composed of two polypeptide chains, with five peptides found after digestion [ 37 ]. Among them, the peptide with the IVELEEELR sequence has been shown to be the most sensitive and was thus chosen to be a marker of tropomyosin [ 37 ]. The alternative method proposed in this paper found glutamic acid to be the most prevalent amino acid in that peptide, and it was thus chosen to be a marker of tropomyosin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…J. Wang et al. (2021) also developed an assay based on high‐performance liquid chromatography‐tandem mass spectrometry (LC–HRMS) to detect crustacean TM qualitatively and quantitatively. They found that this approach demonstrated high accuracy and reproducibility (recovery range of 91−109%, standard deviations < 15%, limit of quantification of 1.6 mg/kg) in various food matrices (chicken sausages, beef balls, and egg–milk biscuits).…”
Section: Detection Methods For Seafood Allergensmentioning
confidence: 99%
“…There are various types of allergic reactions, which can be divided into Type‐I: anaphylaxis, Type‐II: cytotoxic, Type‐III: immune complex, and Type‐IV: late‐onset (Maker et al., 2019; Trautmann & Stoevesandt, 2019). In individuals susceptible to TM, IgE‐mediated allergic reaction (Type‐I allergic reaction) is the most common (Jianhua Wang et al., 2021). The IgE‐mediated hypersensitivity reaction mainly covers two steps based on seafood allergy.…”
Section: Mechanism and Clinical Symptoms Of Tm‐induced Allergic Reactionmentioning
confidence: 99%